The clinical efficacy and safety of equipment-assisted intravesical instillation of mitomycin C after transurethral resection of bladder tumour in patients with nonmuscular invasive bladder cancer: A meta-analysis. - Weijian Zhou; Jianping Liu; Dongdong Mao; Changying Hu; Dianjun Gao (PLoS ONE, 2022)
Background This review and meta-analysis aimed to systematically evaluate the clinical efficacy and safety of equipment-assisted intravesical instillation of mitomycin C (MMC) in patients with nonmuscular invasive bladder cancer (NMIBC) after transurethral resection of bladder tumour (TURBT). Methods The Embase, PubMed, CNKI, CBM, WANGFANG, VIP, Cochrane Library, and Clinicaltrial.com databases were searched for articles published before April 2022. The experimental group was treated with intravesical instillation of MMC assisted by equipment, including radiofrequency-induced thermochemotherapy, conductive thermochemical therapy, electromotive drug administration, or locoregional hyperthermia. The control group was treated with simple MMC perfusion. The outcomes of interest in the meta-analysis were recurrence, progression, side-effects, gross haematuria, and bladder irritation. Results A total of 15 studies that enrolled 1,190 patients were included in the meta-analysis. Compared to that of the control group, device-assisted intravesical instillation of MMC significantly reduced both tumour recurrence (odds ratio [OR] = 0.32, 95% confidence interval [CI] [0.24, 0.42], P <0.00001) and progression (OR = 0.29, 95% CI [0.12, 0.67], P = 0.004). There were no significant differences between the two groups in terms of safety (OR = 1.21, 95% CI [0.66,2.21], P = 0.54), bladder irritation (OR = 1.06, 95% CI [0.72,1.55], P = 0.78), or gross haematuria (OR = 1.11, 95% CI [0.64,1.94], P = 0.72). Conclusions Equipment-assisted intravesical instillation of MMC significantly reduced the recurrence and progression of patients with NMIBC who underwent TURBT and improved their quality of life. Given the significant heterogeneity in research quality and sample size among earlier studies, more prospective, multicentre, large sample randomized controlled trials are needed to supplement and verify this in the future.